Networked territorialism: the routes and roots of organised crime - Clark, Andy (Trends in organized crime, 2021)
In the digital age, space has become increasingly structured by the circuitry of global capital, communications and commodities. This ‘network society’ splinters and fragments territorial space according to the hidden logic of networked global capital; with successful criminal entrepreneurs connecting bases in low-risk, controllable territories with high-profit markets. Drawing on a recent, large-scale study of organised crime in Scotland, in this paper we elaborate the relationship between place, territory and criminal markets in two contrasting communities. The first is an urban neighbourhood with a longstanding organised crime footprint, where recognised local criminal groups have established deep roots. The second is a rural community with a negligible organised crime footprint, where the drug economy is serviced by a mobile criminal network based in England. Through comparison of the historical roots and contemporary routes of these criminal markets, we note both similarity and difference. While both communities demonstrated evidence of ‘networked territorialism’, key differences related to historical and social antecedents, in particular the impact of deindustrialisation.